THE EFFECT OF ARGUMENT QUALITY AND SOURCE CREDIBILITY ON PURCHASE INTENTION WITH CONSUMER-WELL BEING AS A MEDIATING VARIABLE - Amanda Tri Andini; Thamrin Thamrin (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of Argument Quality and Source Credibility on Purchase Intention with Consumer Well-Being as a mediating variable on TikTok users in Indonesia. The phenomenon of the increasing use of influencers in promoting products through TikTok Shop encourages the importance of argument quality and source credibility in influencing consumer purchasing decisions. This study uses a quantitative approach with the PLS-SEM method and involves 150 respondents who are active TikTok users and have purchased skincare products after watching promotional content from influencers Reizuka Ari and Maharaja SP. The results of the study show that Argument Quality has a positive and significant effect on Purchase Intention and Consumer Well-Being. Meanwhile, Source Credibility actually has a negative but significant effect on both variables. In addition, Consumer Well-Being is proven to have a positive and significant effect on Purchase Intention. In terms of mediation, Consumer Well-Being significantly and positively mediates the relationship between Argument Quality and Purchase Intention, but is unable to positively strengthen the relationship between Source Credibility and Purchase Intention